Socio-Economic Impact of Mangrove Ecosystem Protected Area Utilization in Teluk Pambang Village, Bantan District, Bengkalis Regency - Yolandika, Clara; Sofyani, Tince; Hendrik, Hendrik; Hendri, Ridar; Yulianda, Eni; Bathara, Lamun (Fakultas Pertanian, Universitas Riau, 2023)
This study aims to examine the socio-economic impact of mangrove ecotourism area in Teluk Pambang Village. This research was carried out for one month starting from mid-January – February 2023 and was located in the mangrove ecosystem area, Teluk Pamban Village, Bantan District, Bengkalis Regency, The data used in this study were primary data and secondary data. This survey data collection method uses direct interviews with communities who live and work around the mangrove ecosystem area around Teluk Pambang Village. Descriptive analysis was conducted to describe the socio-economic activities of the surrounding community and to explain the condition of mangrove forests in Bengkalis, Riau Province, secondary data obtained. The recommendations raised on the basis of this research are between ecotourism managers and the community to achieve common goals, namely efforts to improve the economy, protect mangrove forests better and form tourism institutions, meaning that cooperation is needed. Another important recommendation is that the government needs to play a role in ensuring the safety and security of tourists inside and outside the region. Key words:Ecotourism, mangroves, socio-economic, Teluk Pambang